Clinician Use and Acceptance of Population-Based Data about Respiratory Pathogens: Implications for Enhancing Population-Based Clinical Practice - Gesteland, Per H (American Medical Informatics Association, 2008)
Front line health care providers (HCPs) play a central role in endemic (e.g., pertussis), epidemic (e.g., influenza) and pandemic (e.g., avian influenza) infectious disease outbreaks. Effective preparedness for this role requires access to and awareness of population-based data (PBD). We investigated the degree to which this is currently achieved among HCPs in Utah by surveying a sample about access, awareness and attitudes concerning PBD in clinical practice. We found variability in the number and nature (national vs. local, pushed vs. pulled) of PBD sources accessed by HCPs, with a subset using multiple sources and using them frequently. We found that HCPs believe PBD improves their clinical performance and that they cannot rely on their own practice to remain informed. These findings suggest that an integrated system, which interprets PBD from multiple sources and optimizes the delivery of PBD, may facilitate preparedness of HCPs through the application of PBD in routine clinical practice.